2002
DOI: 10.1046/j.1439-0523.2002.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between European corn borer resistance and concentration of mycotoxins produced by Fusarium spp. in grains of transgenic Bt maize hybrids, their isogenic counterparts, and commercial varieties

Abstract: The European corn borer (ECB), Ostrinia nubilalis Hb., is a major pest of maize in central Europe and promotes the infection of maize with Fusarium spp. In this study, transgenic Bt maize hybrids were compared with their isogenic counterparts, and with commercial hybrids from the recommended list with regard to their level of ECB resistance and their concentration of deoxynivalenol (DON), its 15‐acetyl (15‐A‐DON) and 3‐acetyl (3‐A‐DON) derivatives, nivalenol (NIV), fusarenon‐X (FUS‐X), fumonisins (FUM), and ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 16 publications
5
39
2
4
Order By: Relevance
“…Some field trials, conducted in the USA in 2000-2002, demonstrated that fumonisin levels were frequently lower in grains of Bt hybrids than in non-Bt varieties (Hammond et al, 2004). Other experiments carried out in central Europe concluded that Bt maize hybrids slightly reduced the fusariotoxin level of maize (Magg et al, 2002). Field studies conducted in Ontario (Canada) showed that deoxynivalenol concentrations were reduced in Bt maize but were mainly dependent on O. nubilalis density in the field (Schaafsma et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Some field trials, conducted in the USA in 2000-2002, demonstrated that fumonisin levels were frequently lower in grains of Bt hybrids than in non-Bt varieties (Hammond et al, 2004). Other experiments carried out in central Europe concluded that Bt maize hybrids slightly reduced the fusariotoxin level of maize (Magg et al, 2002). Field studies conducted in Ontario (Canada) showed that deoxynivalenol concentrations were reduced in Bt maize but were mainly dependent on O. nubilalis density in the field (Schaafsma et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Plant host genotype is known to affect production during plant colonization (33,43,44), and this can be exploited in resistance breeding programs. Host variation is thought to be based on a combination of pathogen growth or infection inhibition and biochemical differences which enable resistant varieties to downregulate DON biosynthesis (47) or to rapidly degrade DON (46).…”
Section: Discussionmentioning
confidence: 99%
“…The host and climatic factors influence the growth, survival, dissemination and hence the incidence of seed borne fungi and the disease severity. The influence of locality, host cultivars, pathogenicity and toxicity of these fungi were extensively studied (Miedaner et al 2001;Magg et al 2002). The influence of climatic factors on the occurrence of seed borne fungi is complicated by the fact that the fungi can infect or cause disease individually or as a complex (Doohan et al 1998).…”
mentioning
confidence: 99%